Understanding the challenges and nature of land administration in the Tamale Metropolis, Northern Region, Ghana (Ghana Journal of Science, Technology and Development, 2022)
Land plays an integral role in almost every economic activity. Land administration, therefore, is critical for the national development of a country. It is the hope and aspiration of many to own landed property for various reasons such as for residential, agricultural, and commercial purposes amongst others. Some African countries over the years have embarked on several land administration and land registration reforms to stimulate growth and reduce poverty amongst its people and these programmes are yielding positive results in some of these countries. This paper used semi-structured questionnaires to elicit information from fifty-one (51) participants in the Tamale Metropolitan Assembly, including traditional leaders, members of the general public who have ever registered their lands with the Lands Commission and Divisional heads at the Lands Commission, through randomly and purposefully selected sampling, respectively. This paper reveals that there are still teething challenges affecting land administration in Tamale which include the cost of land, cost of registration, corruption, weak coordination among land sector agencies, encroachment of state land, poor record-keeping on the land transaction and unidentified traditional land boundaries. This paper recommends effective coordination among land sector stakeholders including the land commission, land use and spatial planning authority and the traditional authorities for meaningful reforms on land administration.